REPRESENTASI KESETARAAN GENDER DALAM IKLAN MINYAK ZAITUN MUSTIKA RATU VERSI: AMANDA MANOPO (Analisis Semiotika Roland Barthes) - Jihan Virlia (2021)
Stereotypes of women in terms of the freedom to have a career and pursue education are often obstacles to expressing and utilizing the potential that exists in women, it is necessary to be aware of gender equality in society that men and women are entitled to equal opportunities because gender roles are a construction or community made. This is the basis for this research with the advertisement of Mustika Ratu Olive Oil Version: Amanda Manopo as the object of research. The purpose of this study was to determine the form of representation and the values of gender equality contained in the Mustika Ratu Olive Oil advertisement Version: Amanda Manopo. This study uses a qualitative approach with semiotic analysis of Roland Barthes, while the theory used is the theory of nurture. The results of this study found that the Mustika Ratu Olive Oil Version: Amanda Manopo advertisement has gender equality values by displaying women's efforts showing that today's reality is different from the roles that are always pinned on women, for example showing the spirit of women's freedom to work, utilizing their potential. , pursue higher education, and strengthen women's self-confidence. Keywords: Advertising, gender equality, representation, semiotics